IMAN TANPA NALAR, BUNUH DIRI NALAR TANPA IMAN, DELUSI - Bambang Sugiharto (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2012)
Both whorsippers of extrem rationalism and religious fundamentalists have the tendency of reducting reality in their mere perspective and approach. On the one hand, the extrem rationalists emphasize their approach to reality based on mere verificative and empirical method in so far as there could be no room for religious explanation. On the other hand, religious fundamentalists face the modern world by purifying their doctrines, strengthening the identity, restrictring their normative principles, and taking religion up to the strategy of politic on freedom. It certainly is critical and crucial to watch on reason and faith in each proportion without tending to absolutize its perspective since any tendency to absolutize perspective reduces human capacity to approach reality naively. Without intense dialog, sooner or later faith and reason will come to any kind of pathology and danger of life.